AMPA, kainate and NMDA ionotropic glutamate receptor expression: an in situ hybridization atlas. - Wisden,W; Seeburg,PH; Monyer,H (Elsevier Science Ltd, 2000)
The volume presents a comprehensive and up-to-date treatise of the glutamatergic synapse and its environment.